Pengembangan Sistem Rekam Medis Pasien Berbasis Web (Studi Kasus : Klinik Rafael Malang) - Himawan Sutanto; Faizatul Amalia; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
There are a lot of medical facilities that use information technology to simplify data storing, one of those technologies is an electronic health record. In Rafael Clinic Malang, the health record process that was done there is still not efficient enough because the process still uses manual writing and excel. The procedure is carried out at least three times, that is, writing the data in a patient visitation book, patient ID, then rewrite the data to excel. The health record data are still kept in patient ID so it need some times to search for the ID, not including if the ID is missing or damaged. Based on those problems, the author developed a web-based electronic health record system. The purpose of this research is to know the result of requirement analysis, design, implementation, and the testing result of the developed system. Waterfall model is used as the development method, which has the principle that the next development stage cannot be carried out if the previous stage has not been completed. 47 functional requirements and one non functional requirement were obtained through requirement elicitation, in which security being the non functional requirement. Designing was done using object oriented approach, which produces sequence diagram and class diagram. Database, algorithm, and interface designing is also done. Unit testing using the white-box method gives 100% valid results. Acceptance testing with the black-box method for 80 test cases got 100% valid results. Integration testing gives 100% valid results. Security testing of electronic payments and login sessions has met expectations.